PROBLEMS OF APPLICATION AND WAYS TO IMPROVE THE LAW ON CRIMINAL LIABILITY FOR CHILD PORNOGRAPHY (Bulletin of criminological association of Ukraine, 2023)
The article is devoted to identifying contradictory provisions in the current law on criminal liability for child pornography, which do not comply with the scientifically determined principles of criminalization of acts, and to developing proposals for improving these provisions.First of all, attention is drawn to the fact that the criminalization of acts under Part 1 of Article 3011 of the Criminal Code of Ukraine is completely unnecessary, as it does not comply with such principles of criminalization as: the principle of social danger, the principle of proportionality of positive and negative consequences of criminalization, the principle of systemic legal consistency, the principle of international legal necessity and admissibility, the principle of prohibition without gaps and excessiveness, the principle of proportionality of sanctions and economy of repression. It is also noted that such a socially dangerous act as offering or providing a child with access to child pornography, including through the use of information and telecommunication systems or technologies, remains uncriminalized. It is also pointed out that the sanctions of article 3011 of the Criminal Code are excessively severe compared to the sanctions of articles providing for liability for similar acts.In order to eliminate the identified shortcomings and bring the provisions of Article 3011 of the Criminal Code in line with the provisions of the Council of Europe Convention on the Protection of Children against Sexual Exploitation and Sexual Abuse (Lanzarote Convention), the Law of Ukraine "On Protection of Public Morality", Articles 1561 and 301 of the Criminal Code of Ukraine, it is proposed to: decriminalize the acts provided for in Part 1 of Article 3011 of the Criminal Code and exclude the provisions of Part 1 from the text of this article; establish criminal liability for offering or providing a child with access to child pornography, including through the use of information and telecommunication systems or technologies; bring the sanctions of Article 3011 of the CC in line with the sanctions of Articles 1561 and 301 of the Criminal Code; leave in Article 3011 of the Criminal Code the provision that a minor shall not be subject to criminal liability for the production of child pornography if such actions are committed without the purpose of sale or distribution.
Keywords: protection of children; child pornography; principles of criminalization; contradictions in legislation; improvement of the law